LYME DISEASE – AN UPDATED REVIEW OF CLINICAL FEATURES, DIAGNOSTIC METHODS, AND THERAPEUTIC OPTIONS - Maraszewska, Ewa; Sztajura, Jędrzej; Szklarski, Maksymilian; Szkarłat, Karol Józef; Targosz, Szymon; Stachel, Michał; Szymacha, Weronika; Płecka, Aleksandra; Zimnicki, Karol; Stępień, Alicja (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and purpose: Lyme borreliosis represents the most common vector-borne disease in temperate regions, with its incidence steadily increasing as a result of climate change and the progressive expansion of tick habitats. This review synthesizes current epidemiological data, explores the complex clinical landscape across different geographic regions, and critically evaluates both the persistent obstacles and recent innovations in clinical and laboratory diagnostics. Description of the state of knowledge: The pathogenesis of Borrelia burgdorferi relies heavily on the immunomodulatory properties of tick saliva and extensive antigenic variation to evade host innate defenses and disseminate systemically. Clinical progression is traditionally categorized into early localized, early disseminated, and late disseminated stages, which can involve the skin, central nervous system, joints, and heart. While the pathognomonic erythema migrans rash allows for a definitive clinical diagnosis, other manifestations depend on a standard two-tiered serological testing algorithm. This indirect testing approach frequently lacks sensitivity during the early stages of infection, complicating accurate diagnosis. Standard management relies on targeted antibiotic therapy, such as doxycycline or ceftriaxone, which successfully resolves active infection. However, for patients presenting with Post-Treatment Lyme Disease Syndrome (PTLDS), prolonged antibiotic regimens offer no sustained clinical benefit and significantly increase the risk of severe adverse events. Conclusions: While early recognition and prompt antibiotic administration consistently yield an excellent clinical prognosis, the inherent limitations of standard serological testing remain a critical diagnostic barrier. Addressing these challenges requires the urgent development and implementation of advanced diagnostic technologies, including host-based biomarkers and rapid point-of-care biosensors. Furthermore, optimal patient management mandates multidisciplinary symptomatic support for post-treatment syndromes, alongside continued research into next-generation vaccines to prevent transmission.